DIGITAL TAX SYSTEMS AND COMPLIANCE: THE IMPLEMENTATION OF CORETAX - Yuliana Gunawan; Maria Natalia; Lukas Theofilus Soen (Jurnal Bisnis dan Akuntansi, 2026)
The direction of this research is to analyze whether Coretax implementation affects individual taxpayer compliance and whether tax reporting efficiency mediates this relationship. Coretax, introduced as part of Indonesia’s digital tax reform in 2025, is expected to strengthen tax administration and improve taxpayer compliance. However, empirical evidence of its effectiveness remains limited because of its recent implementation. This research used the collection of 189 individual taxpayers registered with the Soreang Tax Office (KPP Soreang), Bandung Regency, West Java analyze with quantitative explanatory approaches. Purposive sampling method utilizes for selecting the respondents and were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results imply that taxpayer compliance does not impact significantly from Coretax implementation. However, Coretax implementation strongly influenced tax reporting efficiency which improves taxpayer compliance also. Furthermore, rather than direct system adoption, improved compliance results from greater reporting efficiency since mediation role of tax reporting efficiency in Coretax implementation and taxpayer compliance is confirmed. Contribution to the tax digitization literature by providing one of the first empirical assessments of Coretax implementation in Indonesia and demonstrating the mediating role of tax reporting efficiency in taxpayer compliance done by this research. Practical implications, such as strengthening tax administration reform by improving system efficiency, service quality, and taxpayers digital literacy also offered by this research.